2018
DOI: 10.1002/adsc.201801221
|View full text |Cite
|
Sign up to set email alerts
|

Domino Reactions Initiated by Copper‐Catalyzed Aryl‐I Bond Thiolation For the Switchable Synthesis of 2,3‐Dihydrobenzothiazinones and Benzoisothiazolones

Abstract: The three-component reactions of o-iodobenzamides, elemental sulfur and dichloromethane (DCM) providing 2,3-dihydro-4H-benzo[e][1,3]thiazin-4-ones (2,3-dihydrobenzothiazinones) are accomplished via copper-catalyzed aryl CÀI thiolation and subsequent N-, S-hetero ring formation. In addition, the in situ aryl CÀI bond thiolation is also employed for the switchable synthesis of benzo[d]isothiazol-3(2H)ones (benzoisothiazolones) by subjecting o-iodobenzamides, elemental sulfur to the copper-catalyzed condition wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 65 publications
(40 reference statements)
1
18
0
Order By: Relevance
“…In general, Naryl products 134 a were obtained in higher yields than N-alkyl 134 b, which was tested for only one example. Similar reactivity was previously observed with ochlorobenzamidines [107] and o-bromobenzamides [108] (See section 2.8).…”
Section: 2-and 13-dithioles and Other Sulfa Heterocycles With Sulfsupporting
confidence: 85%
See 2 more Smart Citations
“…In general, Naryl products 134 a were obtained in higher yields than N-alkyl 134 b, which was tested for only one example. Similar reactivity was previously observed with ochlorobenzamidines [107] and o-bromobenzamides [108] (See section 2.8).…”
Section: 2-and 13-dithioles and Other Sulfa Heterocycles With Sulfsupporting
confidence: 85%
“…When benzamides [108] were used in place of benzamidines, Liu et al found that o-iodo derivatives 247 were particularly reactive for a similar transformation, especially in the presence of CuBr 2 as a catalyst (Scheme 86). The expected benzoisothiazole products 248 could be formed for less than 10 min upon microwave irradiation with sulfur and triethylamine.…”
Section: Benzoisothiazolementioning
confidence: 99%
See 1 more Smart Citation
“…The average molecular weight of the copolymer was studied by GPC analysis. 6,21 According to the GPC results, the average molecular weight of compound 4 was found to be 12 580. Table 1 shows the results of the EDX elemental analysis and GPC for all the prepared compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The construction of eight-membered cyclic diaryl suldes via the domino reaction of arynes with thioaurone analogues, 4 toluene oxidation-Knoevenagel-condensation domino reaction, 5 Cu-catalyzed aryl-I bond thiolation for the switchable synthesis of 2,3-dihydrobenzothiazinones and benzoisothiazolones, 6 Cu-catalyzed one-pot synthesis of C-4 sulfonated isoquinolin-1(2H)-ones, 7 and Co-catalyzed diastereoselective diuoroalkylation/Giese addition domino reactions 8 are some of the recently reported applications of the domino approach in organic synthesis. Previously, Chandra et al reviewed the application of domino reactions in catalytic C-C bond formation.…”
Section: Introductionmentioning
confidence: 99%